(untitled) (Culturas Científicas, 2024)
The relevance of studying biological individual differences in relation to health has been progressively increasing, with the current rise of personalized medicine serving as a prime example. In this field, the unique set of characteristics in each individual patient forms the basis for personalized diagnoses and treatments. The objective of this work is to analyze and define the issue of biological individuality in medicine. Biological individuality pertains to the biological uniqueness of every human individual and its impact on clinical decision-making. The qualities of patients being biologically unique in a way that pertains to medicine, with implications for the assessment and clinical decision-making concerning an individual’s health status, will be examined in relation to general medical categories. This examination will primarily focus on evidence-based medicine, randomized clinical trials, and the establishment of reference values in clinical laboratories. It will be argued that the issue of biological individuality in relation to general health categories is fundamentally an epistemological problem related to the external validation of clinical evidence. Additionally, we will explore how the individualization of medicine, with personalized medicine as its current paradigm, represents an attempt to address the previously mentioned issue of biological individuality. Nevertheless, in this context, challenges of both epistemological and metaphysical natures arise, with the latter being associated with the definition of health and disease.